Microscopie Calculations of Nuclear Level Densities and Astrophysical Applications - Demetriou, P.; Goriely, S. (HNPS Advances in Nuclear Physics, 2019)
A new level density formula based on a microscopic calculation of the thermodynamic quantities using the deformed Hartree-Fock-BCS method is proposed. In the microscopic approach shell, pairing and deformation effects on the thermodynamic quantities are treated consistently. The final level density formula is shown to be in close agreement with experimental neutron resonance spacings and low energy states. The impact of the newly-determined level densities on nuclear reaction cross sections and rates of relevance in astrophysics applications is presented.